Rumpelstiltskin Level 4 - Mcilvain, Audrey; Hughes, Annie; Williams, Melanie (England Pearson Education Limited, 2000)
Rumpelstiltskin helps a miller's daughter turn straw into gold. In return, she promises to give him her first child. Can she manage to keep her child?
Keywords: Tham khảo